SYSTEM OF FUNDS IN FUNDS TRAVEL SERVICE BUREAU OF LEGAL SOCIOLOGY PERSPECTIVE - Kholifatun Nur Mustofa (Journal of Islamic Business and Economic Review, 2020)
Umrah is a form of sunnah worship and has the essence of Sharia which is almost the same as the pilgrimage. The difference lies in the time of it is implementation. Hajj is performed in the month of Dhul-Hijjah, while Umrah can be performed at any time. Many aspects of cooperation merely fear Allah provide for the hereafter. One form of cooperation that is common in the community is Umrah bailout services that can be used as a business, which is profitable or often also called Umrah bailout funds are needed by Muslims who have a strong desire to perform Umrah worship but they are limited by their financial condition meaning they can leave Umrah but the payment is more flexible because it is paid in installments or through installments through financial services. Umrah bailout products are used as the choice of the community in performing Umrah worship, Umrah bailout funds whose financing is aimed at people who want to carry out Umrah worship. The high interest of the community to be able to worship the holy land of Mecca, but is constrained by the high enough cost, so it takes a long time to collect the cost to go on pilgrimage, therefore more and more services for Umrah worship providers, it is clear that the sale of Umrah organizers services becomes an industry the religiosity sector, what else is very beneficial for the service bureau.